Transient internally driven aurora at Jupiter discovered by Hisaki and the Hubble Space Telescope. Issue 6 (25th March 2015) - Kimura, T.; Badman, S. V.; Tao, C.; Yoshioka, K.; Murakami, G.; Yamazaki, A.; Tsuchiya, F.; Bonfond, B.; Steffl, A. J.; Masters, A.; Kasahara, S.; Hasegawa, H.; et al.
Abstract: Jupiter's auroral emissions reveal energy transport and dissipation through the planet's giant magnetosphere. While the main auroral emission is internally driven by planetary rotation in the steady state, transient brightenings are generally thought to be triggered by compression by the external solar wind. Here we present evidence provided by the new Hisaki spacecraft and the Hubble Space Telescope that shows that such brightening of Jupiter's aurora can in fact be internally driven. The brightening has an excess power up to 550 GW. Intense emission appears from the polar cap region down to latitudes around Io's footprint aurora, suggesting a rapid energy input into the polar region by the internal plasma circulation process. Key Points: Energy is rapidly supplied to Jovian aurora during the solar wind quiet period Auroral morphology suggests a global change in the auroral process This suggests an internally driven disturbance during the quiet period